Multivariate analysis of the feeling of insecurity generated by national and foreign minors: Encuesta a Fuerzas y Cuerpos de Seguridad del Estado, Profesionales de Intervención Directa con Menores y Población General - Ruiz-Fincias, Mª Inmaculada; Grimaldo-Santamaría, Rolando-Oscar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The data analysis using spatial representation (HJ-Biplot and Multiple Correspondence), orders the perception of insecurity that State Security Forces and Corps, professionals of direct social intervention with minors and population dedicated to other occupations have with respect to the native and foreign youth population in Spain. The results show groupings according to the professional group interviewed and their level of perception of insecurity. The group of the Spanish Armed Forces stands out with a high perception of insecurity, generated with greater intensity by young people from the Maghreb. The main conclusion is that there are notable differences in the perception of insecurity among the groups surveyed with respect to young foreigners and nationals.